Aktivitas Fotokatalitik TiO2 yang Dilapiskan pada Polipropilena Berbentuk Lembaran dan Butiran - Sutisna, Sutisna; Rokhmat, Mamat; Wibowo, Edy; Rahmayanti, Handika Dany; Khairurrijal, Khairurrijal; Abdullah, Mikrajuddin (Jurnal Matematika dan Sains, 2017)
The sheet and granule of polypropylene (PP) have been used as the support material for TiO2 catalyst. The TiO2 powder was coated to the polymer surface using a combination of electrostatic and heating methods (for the PP sheet) and thermal milling method (for PP granule). The photocatalytic testing of catalysts conducted on a 300 ml solution of Methylene Blue (MB) with initial concentration of 25 ppm. Under solar ilumination, the catalyst sheets have a higher photocatalytic activity than the catalyst granules.